Therapeutic misconception and the appreciation of risks in clinical trials - Lidz, Charles W; Appelbaum, Paul S; Grisso, Thomas; Renaud, Michelle (Social science & medicine (1982), 2004)
Studies repeatedly have shown that clinical research subjects have trouble appreciating the implications for their clinical care of participating in a clinical trial. When this failure is based on a lack of appreciation of the impact on individualized clinical care of elements of the research design, it has been called the “therapeutic misconception”. Failure to distinguish the consequences of research participation from receiving ordinary treatment may seriously undermine the informed consent of research subjects. This article reports results concerning appreciation of the risks of trial participation from intensive interviews with 155 subjects from 40 different clinical trials at two different medical centers in the USA. Working from transcripts of the interviews, every statement of a risk or disadvantage of trial participation was identified and coded into one of 5 different categories. Totally, 23.9% of subjects reported no risks or disadvantages in spite of being explicitly asked about them. Another 2.6% reported only incidental disadvantages such as having to drive a long way to get to the experimental site. In all 14.2% reported only disadvantages associated with the standard treatment (usually side effects). Another 45.8% told the interviewer about disadvantages and risks associated with the experimental intervention (usually side effects). Only 13.5% could report any risks or disadvantages resulting from the research design itself, such as randomization, placebos, double-blind designs and restrictive protocols. The results of this research suggest that subjects often sign consents to participate in clinical trials with only the most modest appreciation of the risks and disadvantages of participation.